Does helminth activation of toll-like receptors modulate immune response in multiple sclerosis patients? - Correale, Jorge; Farez, Mauricio F. (Frontiers in Cellular and Infection Microbiology, 2012)
Multiple sclerosis (MS) is an inflammatory autoimmune demyelinating disease affecting the Central Nervous System, in which Th1 and Th17 cells appear to recognize and react against certain myelin sheath components. Epidemiological evidence has accumulated indicating steady increase in autoimmune disease incidence in developed countries. Reduced infectious disease prevalence in particular has been proposed as the cause. In agreement with this hypothesis, we recently demonstrated significantly better clinical and radiological outcome in helminth-infected MS patients, compared to uninfected ones. Parasite-driven protection was associated with regulatory T cell induction and anti-inflammatory cytokine secretion, including increased TGF-β and IL-10 levels. Interestingly, surface expression of TLR2, on both B cells and dendritic cells (DC) was significantly higher in infected MS patients. Moreover, stimulation of myelin-specific T cell lines with a TLR2 agonist induced inhibition of T cell proliferation, suppression of IFN-γ, IL-12 and IL-17 secretion, as well as increase in IL-10 production, suggesting the functional responses observed correlate with TLR2 expression patterns. Furthermore, parasite antigens were able to induce TLR2 expression on both B cells and DCs. All functional effects mediated by TLR2 were abrogated when MyD88 gene expression was silenced; indicating helminth–mediated signaling induced changes in cytokine secretion in a MyD88-dependent manner. In addition, helminth antigens significantly enhanced co-stimulatory molecule expression, effects not mediated by MyD88. Parasite antigens acting on MyD88 induced significant ERK kinase phosphorylation in DC. Addition of the ERK inhibitor U0126 was associated with dose-dependent IL-10 inhibition and reciprocal enhancement in IL-12, both correlating with ERK inhibition. Finally, cytokine effects and changes observed in co-stimulatory DC molecules after helminth antigen exposure were lost when TLR2 was sile